Representation forms for direct and indirect incentive speech acts (on the material of the Italian language) - Melnikova, Lidumila S. (Journal of the Belarusian State University. Philology, 2021)
The question of formal diversity of ways of expressing the incentive intention used in interpersonal communication is highlighted. The principles of the classification of incentive speech acts according to the criteria of direct and indirect ways of implementing the illocutionary goal are proposed and substantiated. The concept of «secondary performative» is clarified in relation to an explicit motive. Based on the material of the Italian language, the most common possible linguistic ways of transmitting direct and indirect incentive intentions are determined, and their quantitative ratio is revealed taking into account lexical and grammatical markers used in the proposition. The results of the study complement the general picture of the representation of the motivating illocutionary function and can be used in teaching the pragmatic analysis of linguistic expressions, the interpretation of the intention of which is to varying degrees related to the context.